C60 fullerene loaded hydroxyapatite-chitosan beads as a promising system for prolonged drug release. (1st November 2019) - Sukhodub, L.B.; Sukhodub, L.F.; Kumeda, M.O.; Prylutska, S.V.; Deineka, V.; Prylutskyy, Yu. I.; Ritter, U.
Graphical abstract: Highlights: Bioactive material includes Hydroxyapatite (HA), Chitosan (CS) and Fullerene C60 . Cell viability test proves no toxicity of 0.3 and 0.15 mg/ml C60 -containing composites. C60 concentration of 0.004 mg/ml provides an antimicrobial effect against S. aureus . C60 ensures a prolonged release of Anaesthesinum up to 18 days. Anaesthesinum release is close to the zero-order kinetic release profile. Abstract: Bioactive composite material in the form of beads, based on natural polysaccharide Chitosan (CS), hydroxyapatite (HA), and C60 fullerene (C60 ), was synthesized under influence of microwave irradiation (MW). The bead is a 3D matrix consisting of CS macromolecules cross-linked with sodium tripolyphosphate with HA and C60 particles immobilized in its structure. XRD and FTIR data confirmed the formation of calcium deficient carbonate substituted HA with needle-shaped nanocrystallites of about 80 nm. MW does not influence CS structure. C60 enhances the beads shape stability. HPLC studies suggest the (up to 18 days) prolonged release of hydrophobic Anaesthesinum from C60 -containing composites. Changing the C60 content allows adjusting the drug release time. The presence of CS and C60 provides the Anaestesinum release profile, according to the calculated correlation coefficient (r = 0.99), close to the zero order kinetic release profile. The inhibition zone test (ZOI) shows the antimicrobial activity of the composites containing 0.004 mg/ml C60 against S. aureus ATCC 25923 and E. coli ATCC 25922 (ZOI 16 ± 1 and 10 ± 2 mm, respectively). Cell viability test indicates no toxicity of 0.3 and 0.15 mg/ml C60 -containing composites.